2016
DOI: 10.5433/1679-0359.2016v37n4supl1p2641
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of lactose content in milk of Holstein and Jersey cows1

Abstract: This study evaluated the factors influencing the variation in the lactose content of milk in Holstein and Jersey herds in Santa Catarina, southern Brazil, using multivariate analysis. Data from 73 dairy herds in the Dairy Herds Improvement Program of the State of Santa Catarina were provided by the Santa Catarina Association of Cattle Breeders (ACCB). A total of 46,242 monthly records of Holstein and Jersey (59 and 41 % of the total records, respectively) cows from 2009 to 2012 were analyzed using multiple cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 21 publications
6
22
0
5
Order By: Relevance
“…However, when occur an increased concentration of somatic cells in milk it causes a decrease in lactose in milk (e.g. MALEK DOS REIS et al 2013;ALESSIO et al, 2016) because this will be a substrate for mastitis pathogens (BLUM et al, 2008). A similar behavior to the results found in this work for milk yield, and increased SCS, have been reported in several studies (MAGALHÃES et al, 2006;NORO et al, 2006;ANDRADE et al, 2007;CUNHA et al, 2008).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…However, when occur an increased concentration of somatic cells in milk it causes a decrease in lactose in milk (e.g. MALEK DOS REIS et al 2013;ALESSIO et al, 2016) because this will be a substrate for mastitis pathogens (BLUM et al, 2008). A similar behavior to the results found in this work for milk yield, and increased SCS, have been reported in several studies (MAGALHÃES et al, 2006;NORO et al, 2006;ANDRADE et al, 2007;CUNHA et al, 2008).…”
Section: Resultssupporting
confidence: 87%
“…It has been reported that high SCC (> 200,000 cells/mL) might cause changes in milk composition than samples with low SCC (≤200,000 cells/ml) (SANTOS et al, 2003). According to Alessio et al (2016) the lactose content in milk is influenced by somatic cell count, as well as others factors such as parity, and season, but is not related to milk yield, fat and protein levels in milk. Malek dos Reis et al (2013) reported that somatic cell count was negatively associated with reduced lactose in milk from Gir cows observing that lactose content was higher in health quarters than in quarters with high SCC.…”
Section: Resultsmentioning
confidence: 99%
“…Entretanto, o grupo 3 apresenta teor de lactose intermediário, quando comparado ao grupo 2, que possui o valor mais baixo de lactose (4,37%). Esse fato pode estar relacionado aos dias em lactação das vacas, visto que, no grupo 2, elas estão com 149 dias, portanto, além do déficit energético, a redução no teor de lactose pode estar relacionada à contagem de células somáticas (Alessio et al, 2016), porém esse indicador de mastite subclínica e clínica tem sido negligenciado nos experimentos de alimentação de vacas leiteiras. Trabalhos científicos envolvendo vacas de leite devem ser realizados de forma sistêmica, ou seja, devem relacionar o metabolismo energético com a qualidade do leite produzido.…”
Section: Arqunclassified
“…A concentração de lactose no leite cru é influenciada por múltiplos fatores como a contagem de células somáticas, a ordem de parição e a estação do ano, devido à variação sazonal na qualidade e na quantidade de alimentos. Uma deficiência nutricional acarretada por redução qualiquantitativa de volumosos em algumas épocas do ano pode representar diminuição significativa nos teores de lactose no leite (35) . A carga fatorial negativa para nitrogênio ureico do leite (NUL) significa que os teores foram mais elevados no inverno.…”
Section: Voges Jg Et Alunclassified
“…Dietas com maior suplementação concentrada e, consequentemente maior teor de energia estão relacionadas à maior produção e estabilidade do leite ao teste do álcool, com redução de LINA (37) , que, por sua vez, estão relacionadas negativamente aos teores de gordura e caseína. Isso pode estar relacionado à menor produção de leite/vaca/dia nas condições de menor oferta alimentar, o que reduz a produção leiteira, aumentando os teores de proteína e gordura, enquanto o teor de lactose não apresenta relação com a produção (35) . Essa maior produção de leite/vaca/dia foi obtida, na sua maioria, em propriedades que utilizavam suplementação concentrada, principalmente energética e proteica, a qual, por sua vez, estava associada às amostras de leite estável, com menor ocorrência de LINA.…”
Section: Voges Jg Et Alunclassified